MYB81, a microspore‐specific GAMYB transcription factor, promotes pollen mitosis I and cell lineage formation in Arabidopsis. (18th November 2019) - Oh, Sung‐Aeong; Hoai, Thuong Nguyen Thi; Park, Hyo‐Jin; Zhao, Mingmin; Twell, David; Honys, David; Park, Soon‐Ki
Summary: Sexual reproduction in flowering plants relies on the production of haploid gametophytes that consist of germline and supporting cells. During male gametophyte development, the asymmetric mitotic division of an undetermined unicellular microspore segregates these two cell lineages. To explore genetic regulation underlying this process, we screened for pollen cell patterning mutants and isolated the heterozygous myb81‐1 mutant that sheds ~50% abnormal pollen. Typically, myb81‐1 microspores fail to undergo pollen mitosis I (PMI) and arrest at polarized stage with a single central vacuole. Although most myb81‐1 microspores degenerate without division, a small fraction divides at later stages and fails to acquire correct cell fates. The myb81‐1 allele is transmitted normally through the female, but rarely through pollen. We show that myb81‐1 phenotypes result from impaired function of the GAMYB transcription factor MYB81 . The MYB81 promoter shows microspore‐specific activity and a MYB81–RFP fusion protein is only expressed in a narrow window prior to PMI. Ectopic expression of MYB81 driven by various promoters can severely impair vegetative or reproductive development, reflecting the strict microspore‐specific control of MYB81 . Our data demonstrate that MYB81 has a key role in the developmental progression of microspores, enabling formation of the two male cell lineages that are essential for sexual reproduction in Arabidopsis. Significance Statement: Sexual reproduction in flowering plants relies on the production of haploid gametophytes that consist of germline and supporting cells. During male gametophyte development, the asymmetric pollen mitosis I (PMI) of an undetermined unicellular microspore segregates these two cell lineages. In this study, we show that the microspore‐specific GAMYB transcription factor MYB81 promotes PMI and therefore has a key role in the formation of the two cell lineages essential for pollen development and plant fertility.